Experimental-numerical assessment of geogrid-EPS systems for protecting buried utilities. Issue 4 (7th June 2019) - Abdollahi, M.; Moghaddas Tafreshi, S. N.; Leshchinsky, B.
Abstract : Expanded polystyrene (EPS) is a lightweight material commonly used in sensitive geotechnical applications, particularly in transportation applications that often see a confluence of buried utilities and traffic loading. This study investigates the behavior and efficacy of EPS geofoam post-beam (PB) systems as a means of protecting underground utilities. The PB system consists of two EPS geofoam 'post' blocks that both protect buried utilities and support a capping EPS beam and soil overburden. Two series of laboratory large-scale model tests of the EPS PB system under both unreinforced and geogrid-reinforced soil cover were conducted to explore the effect of beam thickness, soil cover thickness and density of geofoam blocks on system deformations and stress distributions. Experimental results showed that the EPS PB system was effective in bearing the applied load without transferring it to the utilities below. The improvement in system performance was most pronounced when higher geofoam density, thicker EPS beams, geogrid reinforcement and increased soil cover were used. Three-dimensional finite element (FE) numerical models were developed and validated based on test results, and leveraged to provide insight into internal system behavior and design parameter selection.